Ranking network security threats of academic administrative local area networks at the institution of higher learning in Malaysia - Shaari, Muhammad Shakirin; Puteh, Nurnasran; Hassan, Suhaidi (Universiti Utara Malaysia, 1996)
The advancement and proliferation of computer networks nowadays have prompted for a concern on the issue of security of the whole network operation. The concern applies to both business and academic computer network environments. This paper describes our research about ranking possible network security threats in academic administrative local area network. In the research, the Delphi method which involve formation of a team of experts, is adopted to obtain the ranking order of the possible security threats. The network security threats are ranked in terms of severity and probability of happening. The response from the Delphi team is then sorted using two methods, namely the Comparison Risk Ranking and Simple Summation Method. The ranking of threats will then be used for further investigation regarding those network security threats.